Enhancing Verb Writing Skills in Eighth-Grade Students with Flashcards: A Classroom Action Research in Indonesia: Meningkatkan Keterampilan Menulis Kata Kerja pada Siswa Kelas Delapan dengan Kartu Flash: Sebuah Penelitian Tindakan Kelas di Indonesia - Maharani, Irma Diah; Santoso , Dian Rahma (Indonesian Journal of Education Methods Development, 2023)
This study aimed to enhance regular and irregular verb writing skills in eighth-grade students at a public junior high school in Blora, Central Java, Indonesia, by implementing flashcards as a teaching tool. The research followed the Classroom Action Research (CAR) approach, encompassing planning, action, observation, and reflection. Data collection methods included observation, tests, questionnaires, and interviews. The analysis revealed a significant improvement in students' average scores throughout the research cycles. The use of flashcards not only improved verb writing skills but also heightened students' vocabulary retention and interest in learning. The findings suggest that incorporating flashcards can be an effective and engaging strategy for teaching verb forms, benefiting students' language proficiency and learning experiences. Highlight: Flashcards enhance verb writing skills: The study aims to improve regular and irregular verb writing skills using flashcards in eighth-grade students. Classroom Action Research (CAR) approach: The research follows the CAR method, including planning, action, observation, and reflection to implement flashcards effectively. Significant improvement in test scores: Data analysis shows a notable increase in average test scores from the preliminary study to research cycles, indicating the effectiveness of flashcards in teaching verb tenses. Keyword: Flashcards, Verb Writing Skills, Eighth-Grade Students, Classroom Action Research, Vocabulary Improvement